Serum uric acid/creatinine ratio and 1-year stroke recurrence in patient with acute ischemic stroke and abnormal renal function: results from the Xi'an stroke registry study of China - Zhongzhong Liu; Zhongzhong Liu; Zhongzhong Liu; Dandan Zhang; Dandan Zhang; Lingxia Zeng; Weiyan Guo; Qingli Lu; Qingli Lu; Zhen Lei; Yunlong Hao; Pei Liu; et al. (Frontiers in Neurology)
BackgroundThe relationship between abnormal renal function and serum uric acid levels in patients with acute ischemic stroke (AIS) remains insufficiently explored. Although uric acid is associated with cardiovascular and cerebrovascular risk, the specific link between normalized serum uric acid (SUA/SCr) and stroke recurrence in patients with impaired renal function has not been well studied. This study aims to fill this gap by investigating the association between SUA/SCr and 1-year stroke recurrence in patients with AIS and abnormal renal function.MethodsThis study utilized the ratio of serum uric acid (SUA) to serum creatinine (SCr) to represent SUA levels normalized for renal function. Abnormal Renal function was defined by the estimated glomerular filtration rate (eGFR) < 90 mL/min/1.73 m2. Multivariable Cox regression, curve fitting, and stratified analyses were employed to assess the relationship between SUA/SCr and 1-year stroke recurrence in patients with AIS and abnormal renal function, considering SUA/SCr as both a continuous variable and in quartiles (Q1–Q4).ResultsOf 1,932 enrolled patients (65.3% male; mean age 66.7 ± 11.3 years), each unit of increase in SUA/SCr was associated with a 17% decrease in 1-year stroke recurrence (HR = 0.83, 95% CI 0.73 to 0.96, P = 0.009). Compared to Q1, the Q2 and Q4 groups showed significantly reduced risk in 1-year stroke recurrence (Q2: HR = 0.46, 95% CI 0.27 to 0.79, P = 0.005; Q4: HR = 0.47, 95% CI 0.27 to 0.81, P = 0.007), with a significant trend across all quartiles (P = 0.01 for trend tests). Curve fitting revealed a negative but non-linear correlation. Subgroup analyses showed that in patients with eGFR < 60 ml/min/1.73 m2, Q4 had significantly lower 1-year stroke recurrence risk than Q1 (HR = 0.19, 95% CI 0.04 to 0.86, P = 0.031).ConclusionLow SUA/SCr independently predicts 1-year stroke recurrence in patients with AIS and abnormal renal function, particularly in those with eGFR < 60 mL/min/1.73 m2.